The evolving role of nucleotide-binding oligomerisation domain-like receptor Pyrin Domain 3 inflammasome activation in vascular endothelial cells: a review - Abas, Razif; Basir, Rusliza; Mohd Thani, Suryati; Salihan, Safuraa; Saat, Azmah; Mohamad Zainal, Nurul Hayati; Mohamad Asri, Siti Fadziyah; Ab Razak, Nur Izah; Mohd Nor, Nurul Huda; Kamaruddin, Nur Aqilah (Universiti Sains Malaysia, 2022)
In the vascular wall, defence against pathogenic damage requires a group of monocytes, the endothelium, dendritic cells, macrophages and a subsequent involvement of pattern recognition receptors anticipating damage-associated molecular patterns (DAMPs) to initiate an innate immune response. The endothelium plays a crucial role in regulating the duration, location and extent of the inflammatory cascade to ensure a definitive immune defence. Molecular changes in the expression of chemokines and cell adhesion molecules ensure protective responses against infection and injury. The multiprotein oligomer complex nucleotide-binding oligomerisation domain (NOD)-like receptor pyrin domain 3 (NLRP3) inflammasome plays a key role in the activation of inflammatory processes in response to DAMPs and pattern-associated molecular patterns. As a result of NLRP3 inflammasome activation, caspase-1 is activated and interleukin-1β (IL-1β) is produced. Caspase-1 is the main mediator of inflammatory feedback to tissue injury, and it is engaged both in the initiation of the inflammatory response and in the induction of cell death. NLRP3 inflammasome promotes further inflammatory responses and pyroptosis in the vascular endothelium; thus, its optimum regulation is crucial in cardiovascular homeostasis. This review outlines our current perception of the role of NLRP3 in vascular endothelial cells.